Thiophene-S, S-dioxidized indophenine (IDTO) based donor–acceptor polymers for n-channel organic thin film transistors. Issue 41 (8th April 2016) - Deng, Yunfeng; Quinn, Jesse; Sun, Bin; He, Yinghui; Ellard, Jackson; Li, Yuning
Abstract : Two donor–acceptor (D–A) conjugated polymers, PIDTOBT andPIDTOBTz, based on thiophene- S, S -dioxidized indophenine (IDTO) as the acceptor building block are synthesized for solution processed organic thin-film transistors. Abstract : Two donor–acceptor (D–A) conjugated polymers, PIDTOBT andPIDTOBTz, based on thiophene- S, S -dioxidized indophenine (IDTO) as the acceptor building block are synthesized for solution processed organic thin-film transistors (OTFTs). The influences of the donor unit on the photophysical, electrochemical and electron-transport properties were investigated. These polymers possess very deep highest-occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels due to the strong electron accepting capability of the IDTO moiety. In OTFT devices, both polymers exhibited unipolar n-type charge transport characteristics with electron mobility up to 0.18 cm 2 V −1 s −1 .